Ob dvestoletnici Aragojevega poskusa - Strnad, Janez (Obzornik za matematiko in fiziko, 2010)
François Arago in 1810 tried to measure the change of the light velocity due to tha motion of the Earth. This was the first in a series of similar unsuccessful experiments. At the bicentenary it appears worthwhile to describe Arago's experiment and to elucidate Arago's starting point. To explain the outcome of the experiment Augustin Fresnel introduced the idea of aether drag. Some facts of Arago's life and works are added.
Keywords: hitrost svetlobe; svetloba; zgodovina fizike